Вивчення конструктивно-технологічних параметрів робочих органів комбінованих чизельних глибокорозпушувачів - Лещенко, С. М.; Сало, В. М.; Петренко, Д. І.; Васильковський, О. М.; Лещенко, С. Н.; Петренко, Д. И.; Васильковский, А. М.; Leshchenko, S.; Salo, V.; Petrenko, D.; Vasylkovskyi, O. (ЦНТУ, 2019)
В роботі проводиться систематизація основних найбільш поширених робочих органів чизельних глибокорозпушувачів з критичною оцінкою їх конструктивно-технологічних параметрів. Доводиться, що незважаючи на конструктивну подібність чизельних лап з прямим стояком, що використовуються в серійних ґрунтообробних агрегатах, конструкцію цих робочих органів не можна вважати повністю обґрунтованою, що насамперед відноситься до використання на лапах додаткових робочих органів і елементів та можливості аналітично розрахувати і практично забезпечити задану глибину суцільного обробітку. Наведені залежності, які дозволяють знайти критичну глибину чизельного обробітку, величину зон деформацій, глибину суцільного обробітку та встановлені значення рекомендованих конструктивних параметрів чизельної лапи з прямим стояком. В работе проводится систематизация основных наиболее распространенных рабочих органов чизельных глубокорыхлителей с критической оценкой их конструктивно-технологических параметров. Доказывается, что несмотря на конструктивное сходство чизельных лап с прямой стойкой, используемых в серийных почвообрабатывающих агрегатах, конструкцию этих рабочих органов нельзя считать полностью обоснованной, что прежде всего относится к использованию на лапах дополнительных рабочих органов, элементов и возможности аналитически рассчитать и практически обеспечить заданную глубину сплошной обработки. Приведены зависимости, позволяющие найти критическую глубину чизельной обработки, величину зон деформаций, глубину сплошной обработки и установленные значения рекомендуемых конструктивных параметров чизельных лап с прямой стойкой. Gradual abandonment of application of erosion-hazardous tools is a worldwide trend in soil tillage. The tools include classic ploughs, machines and equipment with spherical disks, milling units and the like. The article deals with the systematization of the most widespread operating elements of chisel deep-tillers with a critical assessment of their structural and technological parameters. The objective of the work is to study the structural and technological parameters of chisel blades of combined deep-tillers for general purpose, depending on the layout of the unit and the structure of the main operating elements. Regardless of the generally accepted tendency to abandon erosion-hazardous tools at the basic tillage stage, chisel deep-tillers, which are an effective substitute for classic heap plowing, do not have fully substantiated functional schemes and recommendations for the design of both major and additional operating elements. At the Department of Agricultural Engineering of Central Ukrainian National Technical University, a functional scheme, design documentation and a series of hinged chisel aggregates were developed. The main operating element of the developed machines is a straight-leg chisel blade, in which, as additional horizontal deformers, which provide alignment of the bottom of the furrow and better pruning of the root systems of plants, the flat wings are set at a certain angle to the direction of movement, and in combination with the chisel, provide ground clearance in the horizontal plane. Taking into account certain generally accepted assumptions and using known dependencies, the formulas were obtained for theoretical substantiation of rational construction and specific parameters of the proposed chisel blade. As a result of the work, the possibility of using operating elements of chisel deep-tiller blades paws with a straight leg and an additional horizontal deformer was proved. On the basis of the conducted research it is established that in loamy soil conditions chisel deep-tillers provide performance within agrotechnical requirements at the velocity of movement of the unit up to 2.5 m/s, the angle of installation of the chisel to the bottom of the furrow is 25… 30º, chisel length is 0.26…0.35 m at the distance between rows of the operating elements in the longitudinal direction 0.45…0.55 m.
Изучение конструктивно-технологических параметров рабочих органов комбинированных чизельных глубокорыхлителей
The Study of Structural and Technological Parameters of the Operating Elements of Combined Chisel Deep-tillers
Keywords: чизельний глибокорозпушувач; зона деформації ґрунту; додаткові деформатори; чизельна лапа з прямим стояком; чизельный глубокорыхлитель; зона деформации почвы; дополнительные деформаторы; чизельная лапа с прямой стойкой; chisel deep-tiller; soil deformation area; additional deformers; chisel blade with straight leg